Pemetaan Isu Strategis Urusan Perangkat Daerah Di Kabupaten Bekasi - Merdi Hajiji; Bambang Rudiansah (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
Regional development problems are the cause of the gap between the development performance currently achieved and what was planned and between what is to be achieved in the future and the real conditions when the planning was made. The formulation of regional development problems is divided into two groups, namely problems in determining regional development priorities and targets and problems in administering regional government affairs. The problem of regional development is the difference in achievement between the development performance currently achieved and what is planned and between what is to be achieved in the future and current conditions. The differences in question can be seen from regional achievement gaps, as well as provincial achievements and general indicator targets in the regional medium term development plan for the 2025-2029 period. This research aims to map strategic issues in regional government affairs in bekasi regency. This research uses a qualitative descriptive research design, where research data is obtained through data collection techniques in the form of interviews, observations and documentation studies. The analysis technique uses descriptive techniques including data collection, data condensation, data presentation, and drawing conclusions. The results of this research are an analysis of strategic issues which are an important and crucial part of the process of preparing regional development plans to complete the stages that have been carried out previously. Identification of appropriate and strategic issues increases the acceptability of development priorities, can be operationalized and can be morally and bureaucratically accountable. Strategic issues regarding regional officials are obtained from both internal analysis in the form of identifying development problems and external analysis in the form of conditions that create opportunities and threats for regional officials in the next five years.